ANCIENT GREEK ARCHITECTURE - D. M. Rakhmanov; G. D. Khodjaeva; S. Mamaruziev (American Journals Publishing, 2023)
The article discusses the high level of development of industry and architecture in BC architecture in BC.
Keywords: architecture, residential construction, surroundings, galleries, loggias, Acropolis, order, ihram, temple.